FINANCIAL WELL-BEING: A WAY TO MAINTAIN LONG-TERM FINANCIAL SECURITY - Apriansah, Andri; Mulyatini, Nurdiana; Prabowo*, Faizal Haris Eko (JURISMA : Jurnal Riset Bisnis & Manajemen, 2022)
Financial literacy has an important role in encouraging improving financial well-being. The purpose of this study is to determine the effect of Financial Attitude and Financial Knowledge on Financial Well Being. The research method uses quantitative and data analysis techniques used is multiple linear regression analysis. With a population of 105 employees of Badan Pengelolaan Keuangan Daerah Kabupaten Ciamis and sampling using a saturated sampling technique, the entire population was sampled with as many as 105 respondents. The research results conclude that financial attitude and financial knowledge affect financial well-being with a magnitude of 65.6%. Therefore, it is expected that the financial sector employees of BPKD Kabupaten Ciamis can maintain and improve their financial attitude and knowledge by implementing financial planning, management, and control to improve their financial well-being. The study has an impact on increasing knowledge about financial behavior in government employees. Keywords: Financial management, financial behavior, financial attitude, financial knowledge, and financial wellbeing